ANALYSIS OF TIRE TYPES AND TREAD DEPTH IN VEHICLES OF M1 AND N1 CATEGORIES OPERATED IN THE SUMMERTIME IN ŠIAULIAI - Astrauskas, Darius (PROFESSIONAL STUDIES: Theory And Practice, 2023)
From the point of view of traffic safety, tires are one of the most important parts of cars. Their wear or choosing the wrong tires quite often becomes the cause of an unfortunate traffic accident. It is especially important to pay attention to the use of the right tires for truck and passenger car drivers, because the car has contact with the road surface only on four surfaces of the human palm. Road traffic safety depends on activities in various areas: education of drivers and other road users, road quality and technical condition of cars. Tires are one of the components of a car. This paper examines grip coefficient characteristics, tire tread patterns and types to determine the condition and types of tires in use.